Correlation analysis and path coefficient studies for fatty acid profile in Indian mustard (Brassica juncea L) - Tushadri Singh; SK Gupta; Ashish Sheera (Journal of Oilseed Brassica, 2026)
In the present study, one hundred seventy-five genotypes of Indian mustard (Brassica juncea) were analyzed for itsmajor fatty acid traits using correlation coefficient and path coefficient to examine the cause and consequencesrelationship with direct and indirect components. 175 F plants formed by crossing Pusa mehak (Indian genotype) × 2:3Primus (East-European genotype) and selfing the F s and F s were utilized for this study. The correlation coefficient of 1 2the major fatty acids revealed that there was positive correlation and significance for stearic acid and oleic acid (0.67),palmitic acid and linoleic acid (0.60), linolenic and oleic acid (0.50). While significant negative correlations existedbetween erucic acid and all other fatty acids except eicosenoic acid (0.41). It was also established that a reduction inerucic acid exhibits an elevation in both oleic and linoleic acids and a simultaneous decrease in eicosenoic acid. In pathcoefficient studies, when oil content as dependent character and all other residual 7 fatty acids percentage wasconsidered as independent contributing characters, eicosenoic acid (G= 0.76 ,P=0.73) and oleic acid (G= 0.72, P=0.71)displayed high order of direct effect on oil content and it is followed by linolenic (G= 0.55, P= 0.53), erucic acid (G=0.47, P= 0.46), linoleic acid (G= 0.35, P= 0.33). These characters also been identified as major direct and indirectcontributors towards oil contents and fatty acid profile in Indian mustard. The variation in grain yield unexplained by theseven causes was considered to be due to residual effect (G= 0.28, P= 0.31), which is uncorrelated with other relatedfactors.